Multi-class urinary antibiotic exposure, dietary sources, and childhood overweight and obesity risk through lipid metabolic disruption: evidence from multicenter cohorts in China - Xinli Song; Jieyu Liu; Li Chen; Yi Zhang; Ruolin Wang; Jianuo Jiang; Lan Zhang; Yanle Xiong; Jingyang Su; Ziqi Dong; Yang Qin; Dengcheng Zhang; et al. (Environmental Pollution, 2026)

Discovery and engineering of a formate dehydrogenase with enhanced bicarbonate reduction activity - Feng Lu; Runxin Liang; Yimiao Chen; Xiao Li; Ruolin Yang; Yuhong Huang; Wangtao Jiang; Yongtong Feng; Ping Gui; Xuefeng Wang; Fuqiang Ma (Bioresource Technology, 2026)

Fabrication of microwave-absorbing MFe2O4@sepiolite (M = Mn, Mn0.5Ni0.5, Ni) nanorods with enhanced catalytic performance for degradation and assessment of intermediate toxicity - Ruolin Ni; Lei Jiang; Jinhui Lin; Dan Wu; Keming Zhang; Lu Fu; Zhaohong Zhang; Fang Ma; Yongcai Zhang (Applied Clay Science, 2026)

Unlocking catalytic capacity of (S)-selective ω-transaminases toward aryl methyl ketones via pocket engineering and droplet screening - Ping Gui; Xiao Li; Wangtao Jiang; Ruolin Yang; Peiyao Chang; Xingwang Qie; Xinrui Wang; Xuefeng Wang; Jingjie Jiang; Liyan Wang; Xiaojie Guo; Hongbin Zou; et al. (Bioresource Technology, 2026)

A regulatory biomimetic nanoparticle targeting senescent glioma cells for BNCT treatment - Qi Dai; Zhicheng Zhang; Zhiqing Ben; Xiaoyan Sun; Yufan Yang; Yaxin Qin; QiYao Yang; Xiaoyan Bao; Linjie Wu; Ruolin Jiang; Xin Tan; Xufang Ying; et al. (Chemical Engineering Journal, 2026)

Grassland soil seed bank responses to grazing exclusion: a global synthesis - Jishuai Su; Lixin Yu; Rui Tian; Wanbing Liu; Ruolin Zhao; Menghan Niu; Zekai Yang; Yi Zhang; Fengwei Xu; Heyong Liu; Yong Jiang (Journal of Environmental Management, 2026)

Evaluation of the Degradation Effect of Zearalenone in feed by Bacillus amyloliquefaciens H6 and its Detoxification in Mice - Ruolin Wang; Kaiwei Geng; Yuxuan Liu; Yang Liu; Yujie Gong; Ruirui Jiang; Yadong Tian; Xiangtao Kang; Xiangli Sun; Yanbin Wang (Current Microbiology, 2025)

Luminescence dating of core sediments from the southern coastal Bohai Sea, China, and its implications for transgression history during the Late Quaternary - Zhiqiang Xu; Yang Han; Bingpeng Yan; Mingbo Li; Ruolin Jiang; Ruonan Tian; Bohui Liu; Zihui Zhu; Weitao Yuan; Zhongping Lai (Frontiers in Marine Science, 2025)
Several marine strata have developed along the southern coastal Bohai Sea since the Late Quaternary, preserving abundant records of sedimentary evolution. This region is ideal for studying the sedimentary history of a river–sea interaction area. However, detailed sedimentological and chronological studies remain limited, mainly focusing on the estuaries of the Mihe River. In this study, 12 optically stimulated luminescence (OSL) samples were collected from the upper 20 m of a 101 m core to establish a chronological framework using quartz OSL dating. Grain-size analysis was also conducted to determine sedimentological characteristics. Results indicate that the quartz OSL ages range from >100 ka to 6.2 ± 0.4 ka, and we believe they were the minimum ages when equivalent dose (D e ) >ca. 250 Gy (sample DZK3-G07 and below) owing to OSL signal saturation. Our findings reveal a sedimentary hiatus between >100 ka and 19.8 ka. Holocene sediments are found above a depth of 8.4 m with an onset age of approximately 10.5 ka. A lacustrine layer (8.4–9.6 m) in core DZK3 was dated to 19.8–10.5 ka, which is much older than that of the limnetic and lagoon layers in other cores in this area. Based on sedimentary facies and dating results, no transgressive sediments were observed during marine isotope stage (MIS) 3, and T2 (Xianxian transgression) in the southern coastal Bohai Sea only occurred in MIS 5e. This sedimentary sequence pattern is consistent with global sea-level changes.

Ecological diversity and metabolic strategies of widespread Marinisomatota in global oceans - Shizheng Xiang; Jianyang Li; Zhen Chen; Ruolin Cheng; Liping Wang; Libo Yu; Guangshan Wei; Xiangyu Guan; Brandon R. Briggs; Gary King; Hongchen Jiang; Zongze Shao (Marine Life Science & Technology, 2025)

Functional analysis of a rice 12-oxo-phytodienoic acid reductase gene (OsOPR1) involved in Cd stress tolerance - Longying Wu; Ruolin Wang; Mingyu Li; Zhiye Du; Yufan Jin; Yang Shi; Wenjun Jiang; Ji Chen; Yuan Jiao; Binhua Hu; Jin Huang (Molecular Biology Reports, 2024)

Characterization of MKK family genes and their responses to temperature stress and Vibrio parahaemolyticus infection in noble scallop Chlamys nobilis - Yetao Zeng; Ruolin Jiang; Jingwen Deng; Dewei Cheng; Weili Wang; Jianming Ye; Cheng He; Chuanxu Zhang; Hongkuan Zhang; Huaiping Zheng (Marine Environmental Research, 2024)

Environmentally persistent free radicals on photoaging microplastics shortens longevity via inducing oxidative stress in Caenorhabditis elegans - Hui Li; Yongqi Jiang; Yulun Gu; Chao Chen; Jun Yu; Chen Wang; Chongli Shi; Ruolin Pan; Haibo Chen (Chemosphere, 2024)

Physiological properties evaluation and exopolysaccharide biosynthesis of Limosilactobacillus fermentum JL-2 from Chinese traditional fermented dairy product based on genomic insight - Ruolin Yuan; Lai Jiang; Ruonan Liu; Yanfeng Tuo; Guangqing Mu; Shujuan Jiang (Food Bioscience, 2024)

Association of the external environmental exposome and obesity: A comprehensive nationwide study in 2019 among Chinese children and adolescents - Li Chen; Yang Qin; Yi Zhang; Xinli Song; RuoLin Wang; Jianuo Jiang; Jieyu Liu; Tongjun Guo; Wen Yuan; Zhiying Song; Yanhui Dong; Yi Song; et al. (Science of The Total Environment, 2024)

Differentiated impacts of short-term exposure to fine particulate constituents on infectious diseases in 507 cities of Chinese children and adolescents: A nationwide time-stratified case-crossover study from 2008 to 2021 - Li Chen; Wen Yuan; Mengjie Geng; Rongbin Xu; Yi Xing; Bo Wen; Yao Wu; Xiang Ren; Yue Shi; Yi Zhang; Xinli Song; Yang Qin; et al. (Science of The Total Environment, 2024)

Chronology of core sediments from the south coastal Bohai Sea of eastern Asia and its implications for sedimentary history - Weitao Yuan; Lifang Jiang; Ruolin Jiang; Ruonan Tian; Zhaojing Ding; Zhongping Lai (Quaternary Geochronology, 2024)

Preparation of casein hydrolysate by two-step enzymatic hydrolysis and its immunomodulatory activities in vitro and in vivo - Yutong Jiang; Siyi Li; Ruolin Yuan; Yanfeng Tuo; Guangqing Mu; Shujuan Jiang (Food Bioscience, 2024)

Environmentally persistent free radicals on photoaged nanopolystyrene induce neurotoxicity by affecting dopamine, glutamate, serotonin and GABA in Caenorhabditis elegans - Hui Li; Yulun Gu; Yongqi Jiang; Ping Ding; Xiaoxia Chen; Chao Chen; Ruolin Pan; Chongli Shi; Susu Wang; Haibo Chen (Science of The Total Environment, 2024)

Exploring the associations between phthalate exposure and cardiometabolic risk factors clustering among children: The potential mediating role of insulin-resistant-related genes DNA methylation - Jieyu Liu; Jieyun Song; Di Gao; Yanhui Li; Tongjun Guo; Wen Yuan; Manman Chen; Li Chen; Yi Zhang; Qi Ma; Mengjie Cui; Xinli Song; et al. (Journal of Hazardous Materials, 2024)

Microbial colonization of microplastics in wastewater accelerates the aging process associated with oxidative stress and the insulin/IGF1 signaling pathway - Haibo Chen; Mengfan Chen; Yulun Gu; Yongqi Jiang; Ping Ding; Chen Wang; Ruolin Pan; Chongli Shi; Hui Li (Environmental Pollution, 2023)

Dissection of genetic factors underlying grain size and fine mapping of QTgw.cau-7D in common wheat (Triticum aestivum L.) - Zhaoyan Chen; Xuejiao Cheng; Lingling Chai; Zhihui Wang; Ruolin Bian; Jiang Li; Aiju Zhao; Mingming Xin; Weilong Guo; Zhaorong Hu; Huiru Peng; Yingyin Yao; et al. (Theoretical and Applied Genetics, 2020)

Anaerobic digestion of tobacco stalk: biomethane production performance and kinetic analysis - Lyu Li; Ruolin Wang; Zhenlai Jiang; Wanwu Li; Guangqing Liu; Chang Chen (Environmental Science and Pollution Research, 2019)